Burden and challenges in managing TB infection among people with occupational exposure to silica in India - B. Kalottee; P. Mahajan; A. Nuken; D. Nair; P. Thekkur; A.M.V. Kumar; V. Rai; M. Parmar; H. Solanki; R. Rao; S.K. Mattoo; R. Kumar (IJTLD Open)
BACKGROUND: Occupational exposure to silica increases the risk of TB infection (TBI) and disease. This study aimed to determine the prevalence of TBI and explore challenges in TBI management in such individuals in two districts of India during 2023. METHODS: This was an explanatory mixed-methods study with a quantitative cohort design and qualitative descriptive in-depth interviews. RESULTS: Among 1,555 individuals with occupational exposure to silica, 593 (38%, 95% CI 36–41) underwent interferon-gamma release assay (IGRA) for TBI, of whom 255 (43%, 95% CI 39–47) were found IGRA-positive. Males with occupational silica exposure for ≥20 years had a significantly higher risk of TBI. Of these 160 individuals eligible for TB preventive therapy (TPT), 153 (96%, 95% CI 92–98) were initiated on TPT and 124 (81%, 95% CI 74–88) completed TPT. The low uptake of IGRA was attributed to the stigma associated with TB and reluctance to undergo any medical evaluation. CONCLUSIONS: Compared to the general population, individuals with occupational exposure to silica have an almost two times higher prevalence of TBI. Further research is required to identify the threshold of silica exposure to be considered for screening for TBI. Efforts to increase awareness and decrease stigma can improve the uptake of testing for TBI and TB disease.